Investigating the Multilingual Linguistic Landscape on Local Food Packaging in China: A Three-Dimensional Analytical Model - Yu, Muying; Petrus Atin, Veronica; Shak, Priscilla (Forum for Linguistic Studies, 2025)
As the process of globalization continues to deepen, multilingualism has increasingly permeated various aspects of Chinese society, with local food packaging emerging as a particularly prominent site of linguistic display. The multilingual linguistic landscape on food packaging serves both informational and symbolic functions. However, in practice, its presentation often reveals discrepancies with current language policy in China. This study employs Trumper-Hecht’s three-dimensional analytical model to examine the multilingual linguistic landscape on local food packaging in China. It aims to uncover discrepancies between the linguistic landscape and official language policy, as well as consumers’ perceptions and attitudes toward these discrepancies. Drawing on the field investigation method, the study collected 944 food packaging samples and conducted a questionnaire with 114 valid responses. Quantitative analysis of the packaging samples revealed that approximately 22% featured foreign-language text(s) in a larger font than Chinese, while a similar proportion lacked corresponding Chinese translations for the foreign-language content. Descriptive analysis of the questionnaire data suggests that consumers’ perceptions and attitudes toward these discrepancies are neither clear nor consistent. While most respondents acknowledge the existence of such issues, the overall level of concern is relatively low, and explicit expressions of opposition are limited—particularly in cases where foreign-language text(s) appear in a larger font than Chinese. This subdued public response may, to some extent, contribute to the persistence and growing visibility of such linguistic deviations over time. The findings suggest that relevant authorities need to strengthen supervision of food manufacturers, establish and enforce clearer regulatory systems, and enhance public awareness through targeted campaigns.